General practitioner contacts with patients before and after deliberate self harm. - Houston, K; Haw, C; Townsend, E; Hawton, K (2003)
BACKGROUND: Deliberate self harm (DSH) is an increasingly common problem. Although much attention is focused on suicide prevention by psychiatric services, the role of the general practitioner (GP) in the prevention of suicidal behaviour and in the aftercare of DSH patients is also important. AIM: To examine the nature and timing of GP contacts with DSH patients before and after an episode of DSH, and patients' satisfaction with these contacts. DESIGN OF STUDY: Structured interviews with patients shortly after an episode of DSH and again approximately one year later. SETTING: A representative sample of 139 DSH patients presenting to a district general hospital. METHOD: Patients were interviewed shortly after DSH and at follow-up about GP contacts, prescribed medication and psychiatric symptoms. RESULTS: At the time of DSH, 91.4% of patients were diagnosed with a psychiatric disorder (depression 69.8%), with 28% receiving treatment from psychiatric services. Two-thirds of patients had been in contact with their GP in the month before DSH, but only 13.3% reported expressing suicidal thoughts. Patients consulted their GP in the week following DSH in 40.6% of cases. Over half (57.9%) the patients discussed the reasons for their DSH at the first consultation and 69.5% reported that this was helpful. Overall, 64.3% of patients were satisfied with the follow-up consultations. CONCLUSIONS: The major role of the GP in the prevention of suicidal behaviour is in the detection and treatment of depression, and in the aftercare of DSH patients.